Chinese Breast Milk Fat Composition and Its Associated Dietary Factors: A Pilot Study on Lactating Mothers in Beijing - Wu, Wei; Balter, Adi; Vodsky, Victoria; Odetallh, Yatreb; Ben-Dror, Gai; Zhang, Yumei; Zhao, Ai (Frontiers in Nutrition, 2021)
Regional differences were found in breast milk composition. This study intended to profile the composition of fatty acid (FA) and triacylglycerol (TAG) in Chinese breast milk and to explore its association with maternal diet. Breast milk samples and data of 52 lactating women at 60–90 days postpartum were collected. The FA composition was measured using gas chromatography–flame ionization detection (GC-FID), and the TAG profile was detected by an ultra-performance liquid chromatography system, coupled with accurate-mass quadrupole time-of-flight mass spectrometer. A semi-quantitative food intake frequency questionnaire and a one-time 24-h dietary recall were used to evaluate the previous month's and the short-term dietary intake, including dietary patterns, food groups, and nutrients. Oleic–palmitic–linoleic (OPL) is the most predominant TAG within the Chinese human milk, followed by oleic–palmitic–oleic (OPO), with an average OPL-to-OPO ratio of 1.35. Linoleic acid (LA) and oleic acid (OA) accounted for 23.9 and 32.0% of the total FAs, respectively. Among the food groups consumed during the preceding month, LA content was positively associated with the consumption of soybeans and soybean products (r = 0.311, p = 0.030), whereas a negative correlation was identified with seafood consumption (r = −0.302, p = 0.030). Negative correlations were found between the OA content and the consumption of soybeans and soybean products (r = −0.363, p = 0.009), livestock and poultry meat (r = −0.375, p = 0.006), nuts (r = −0.305, p = 0.028), as well as cooking oil (r = −0.445, p = 0.001). No significant associations were identified between the LA and OA contents and the dietary patterns. This study confirmed a high OPL level in Chinese breast milk and revealed associations of FAs with maternal dietary intake.